Beyond virtue ethics : a contemporary ethic of ancient spiritual struggle - Meawad, Stephen M. (Moral traditions series., 2023)
"This book develops a contemporary model of spiritual struggle aimed at perpetual ascent to and in God. Spiritual struggle in this project, which ultimately shifts the emphasis from virtue's acquisition to its pursuit, is defined as the exertion of effort in all conceivable dimensions-physical, emotional, psychological, intellectual, and spiritual-with intent to attain a semblance of, knowledge of, and intimacy with Jesus Christ in community, for God and for others. Gregory of Nyssa's theory of epektasis assumes a basic three-tiered conception of perpetual ascent, beginning with purification and detachment from fleshly passions, strengthening the soul by increasing in similitude to God, and ending with unity with God, that is, with inexpressible and transformative experience of God. God-the infinite, the Good, and the Paragon of virtue-functions as the orienting principle of this perpetual ascent, mitigating the issues of the unity of the virtues and the self-centeredness and self-effacement of virtue. This book goes on to provide two of many potential concrete instantiations of this suggested model. The first is the application of this model to the body, which in turn will have implications for contemporary sexual ethics. The second is a reintegration of ethics and Scripture through the contemporary application of an ancient Patristic lectio divina"--